Implementasi Metode Exponential Smoothing Pada Sistem Informasi Peramalan Penjualan Produk Olahan Daun Kelor Untuk Meningkatkan Efisiensi Produksi - Alsyah Harahap, Dymas Fatthur Rohim; Putri, Raissa Amanda (Institut Teknologi Garut, 2025)
PT. Keloria Moringa Jaya, based in Medan, North Sumatra, is engaged in the processing and distribution of products made from moringa leaves (Moringa oleifera). The company is still constrained by the lack of an organized sales recording system, making it difficult to monitor performance, analyze trends, evaluate marketing strategies, and make the right business decisions. This study aims to apply the exponential smoothing method in the sales forecasting information system at PT. Keloria Moringa Jaya. This method is used to forecast product sales based on the company's historical data. The sales data used covers the period from May 2024 to April 2025 with a total of 12 monthly data. The system was developed using the Laravel framework and is equipped with features for inputting product data, sales data, and alpha parameter data, as well as displaying the forecast results and their accuracy values. The test results show that the MAD, MSE, and MAPE values for all products are in the accurate category. This research provides practical contributions to the company in supporting more efficient production decision-making and sales strategies.